“God is dead” and the question of science in Nietzsche - Choque Aliaga, Osman Daniel (Estudios de Filosofía, 2019)
This article aims to establish a relationship between the phrase “God is dead” and the theme of science in Nietzsche. For this purpose, an analysis of the phrase “God is dead” will be provided in the light of the recent interpretation put forward in the German world. Secondly, we will deal with the concepts of absence and chaos to determine if these notions can be considered as a further step to the “death of God”. Finally, we will review the subject of science: Nietzsche’s views on it, the implications that stem from its works and, above all, the direct nexus of science with that death. The link between these themes leads to a new understanding of the philosopher of Röcken and the future of research on his philosophy.